Strengthening the Fund's Ability to Assist Low-Income Countries Meet Balance of Payments Needs Arising from Sudden and Exogenous Shocks : Supplement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The G-8 debt relief proposal, if adopted, should have little impact on the rational and operational aspects of the shocks window, but it may affect some of the financing consideratins, which are taken up in the page on "The G-8 Debt Cancellation Proposal and its Implications for the Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt Relief Proposal; Financing Consideration; Financing; PP; PRGF Augmentation